Deadline - Chevigny, Katy.; Amsterdam, Anthony; Bright, Stephen, 1947-; Cabana, Donald; Cross, Tom.; Gauger, Gary. (USA Arts Engine, 2004)
Proving that a documentary can be both rigorous and stylish, Deadline delves into the hot-button topic of the death penalty, with particular focus on the 2002 investigation initiated by former Republican governor of Illinois, George H. Ryan, after an investigative journalism class at Northwestern University proved that three men on Illinois' death row were innocent. The current debate focuses not on the moral right-or-wrong of capital punishment, but on whether the legal system can keep an innocent man from being condemned to death. The debate is by no means simple, and Deadline presents a balanced picture, interviewing lawyers, anti-death penalty advocates, politicians, and men who've been released from death row, all of whom are lucid and articulate. But it's testimonies from victims that are the most emotionally wrenching--and you may be surprised by their statements. A superb documentary, directed by Katy Chevigny and Kisten Johnson.
Language: English Subtitles: Chinese, English, Spanish, Thai, Malay
Keywords: Documentary